The Psychology of Financial Crime: A Critique - Umanhonlen Ogbeiyulu Felix (Sumerianz Journal of Business Management and Marketing, 2020)
The aim of this assessment paper was to critique psychology of financial crime. The study attempts to review psychology of crime and criminal behavior. The paper presents detailed evaluation of works done on the subject matter by prominent psychoanalyst, psychologist and eminent authors. The paper streamlines causes and reasons for crimes, financial crime and criminal network. Specifically, it relates genetic and criminal behaviours to psychological crime behaviour, and domesticates integrated new genomic discoveries into psychological antisocial behaviour. Moreso, the paper identifies basis for future research, reviewed relevance topics, tracing the origin and revolution of crime, and highlights major works as oppose to profound adoptive research. Hence, relevance points on issue in contention within the scope of discussion were also highlighted which lay hold on key factors as juxtaposes criminality and crime, genetics and psychology. However, it concludes that opinion from the genetic of crime and criminality presents a robust critique to the study of psychological crime and criminal behavior reference to relevant school of thoughts. It therefore, propose that the proponents of psychological of crime thesis ought to consider the effect of changes that occur at childhood overtime as a result of religious, communal or counseling efforts, rules and regulations, good governance, harnessed governmental social welfare packages, improved and enhance wellbeing. Others are standard of living which ordinarily brought about by hard works, good conscience and sensitize social life, ratchet effect and paradigm shift.as oppose to environmental related factors and other genetics antidotes.
International Journal
Keywords: Crime and criminality; Psychology; Genetic; Financial; Blue chip crime